"A Problem Like This Is Not Owned by an Individual": Affected Family Members Negotiating Positions in Alcohol and Other Drug Treatment. (June 2018) - Selbekk, Anne Schanche; Adams, Peter J.; Sagvaag, Hildegunn
The main aim of this article is to explore the dynamics of encounters between treatment institutions and families dealing with substance use. What kind of possibilities do such encounters offer, and what kind of processes do they facilitate? Based on interviews with 10 families recruited from three alcohol and other drug treatment centers in Norway, positioning theory is used as an analytical tool to address the dynamics and negotiation (1) between service providers and families when it comes to the possibilities for treatment and support and (2) between family members during the course of treatment. Three main storylines are analyzed in interviews with families about encounters with treatment: (1) the medical storyline, (2) storylines of autonomy, and (3) storylines of connection. These storylines positioned affected family members, respectively, as outsiders, as in need of help in their own right, and as part of an affected family. The medical storyline is revealed as being insufficient to deal with the problems associated with substance use—it needs to be extended by family-involving storylines facilitating processes of reintegration and repositioning within families.